A review on waste derive heterogeneous catalyst for Fenton-like oxidation process / Mohamad Helmi Mohd Asbi and Dr. Norhaslinda Nasuha - Mohd Asbi, Mohamad Helmi; Nasuha, Norhaslinda (2020)
Fenton process is one of the most popular method used to treat organic wastewater where Fe2+ is used as catalyst and hydrogen peroxide (H2O2) as an oxidant. İn this comperative study, a waste derived heterogeneous catalyst from many type of materials such as metal waste and agricultural waste were analyse. The aims of this study is to review the potential of waste derived heterogeneous catalyst for the removal of organic pollutant in wastewater and to analyse the limitation of the potential waste derived heterogeneous catalyst for Fenton-like process. The data used in this study were the secondary sources such as online journals and articles and online books. Process parameters such as pH, catalyst dosage, H2O2 concentration, initial dye concentration and temperature were reviewed. From the results, catalyst derived from waste material can degrade more than 90% of the organic pollutant in the wastewater. The result also shows that the catalyst can operates at wider pH range. İnstead of using room temperature, some of the waste derived catalyst can also operates at temperature more than 40 ºC. Lastly, the used of waste derive heterogeneous catalyst can reduce the cost of operating and reduce the amount of solid waste send to the landfill. Hence, it is a good practice to save the environment.